CRUSTAL DENSITY STRUCTURE OF THE MIZUHO PLATEAU, EAST ANTARCTICA FROM GRAVITY SURVEY IN 1992 - カナオ, マサキ; カミヤマ, コウキチ; イトウ, キヨシ; KANAO, Masaki; KAMIYAMA, Kokichi; ITO, Kiyoshi (National Institute of Polar Research, 1994)
P(論文) Gravity measurements with a LaCoste & Romberg gravity meter were conducted on the Mizuho Plateau along the traverse routes from Syowa Station (69.0°S, 39.6°E) to Dome-F (77.4°S, 39.6°E) by the 33rd Japanese Antarctic Research Expedition (JARE-33) in 1992. Free-air and simple Bouguer gravity anomalies based on gravity disturbance along the traverse routes were obtained by use of both surface elevation data from GPS positioning and bedrock elevation from radio-echo sounding. A density model of crustal structure between Syowa and Mizuho Stations was derived on the basis of the P-wave velocity model from the refraction explosion experiments in 1980 and 1981. The structure of the southern part of Mizuho Station was derived from only gravity anomaly data. The simple Bouguer gravity anomaly was calculated by assuming the layered structure to fit the observed Bouguer anomaly. Increase of the Bouguer anomaly by about -200 mgal from Syowa toward the Dome area indicates crustal thickening of about 40 to 48km. The resultant Moho depth beneath the Dome area is rather large compared with the averaged ones (40-45km) over the continental area in East Antarctica. departmental bulletin paper